How does a simulated soccer match affect regional differences in biceps femoris muscle architecture? - Gonçalves, Basílio A. M. (2017)
Soccer is played by thousands of athletes across the globe and its participation increases the overall risk of injury, in particular, hamstring strain injuries (HSI). Biceps femoris (BF) has been shown to be involved the in 5 out of 6 HSI cases and risk factors including fatigue and short BF fascicle length (FL) have been identified. Furthermore, previous studies suggest that different muscle regions may undergo different strains during dynamic tasks, which could contribute to injury risk. The primary aim of this study was to evaluate the effects of a soccer match on regional differences in the BF muscle architecture. A secondary aim was to assess the reliability of the extended field of view (EFOV) 2D ultrasound imaging to measure muscle architecture parameters.